The Reality of Arabic Teachers in the Intermediate Stage Using Active Learning Strategies from the Point of View of Supervisors - Yassir Kadhum, Maryam (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the current research was to identify the reality of the use of Arabic teachers in the intermediate stage of active learning strategies from the point of view of supervisors, and to achieve the goal of the research, the researcher chose the descriptive approach. As for the research community, it was composed of 140 specialized educational supervisors; the questionnaire was presented to the exploratory research sample, and their number was 40 supervisors. The final form of the questionnaire consists of (12) paragraphs. After excluding the exploratory sample, the research tool was applied to the basic application sample of (100) specialized educational supervisors. The researcher used statistical means, and in light of the research results, the researcher concluded a number of conclusions, recommendations, and proposals.